Interactive Effects of Infant Gestational Age and Infant Fussiness on the Risk of Maternal Depressive Symptoms in a Nationally Representative Sample. - Quist, Megan; Kaciroti, Niko; Poehlmann-Tynan, Julie; Weeks, Heidi M.; Asta, Katharine; Singh, Priya; Shah, Prachi E. (Academic Pediatrics, 2019)
To examine the interactive effects of gestational age and infant fussiness on the risk of maternal depressive symptoms in a nationally representative sample. Our sample included 8200 children from the Early Childhood Longitudinal Study, Birth Cohort. Gestational age categories were very preterm (VPT, 24–31 weeks), moderate/late preterm (MLPT, 32–36 weeks) and full term (FT, 37–41 weeks). Maternal depressive symptoms (categorized as nondepressed/mild/moderate-severe), from the modified Center for Epidemiological Studies Depression Questionnaire, and infant fussiness (categorized as fussy/not fussy) were assessed at 9 months from parent-report questionnaires. We examined the interactive effects of infant fussiness and gestational age categories and estimated adjusted odds ratios (aOR) and 95% confidence intervals (CI) of maternal depressive symptoms using multinomial logistic regression. Infant fussiness interacted with gestational age categories in predicting maternal depressive symptoms (P =.04), with severity varying by gestational age and infant fussiness. Compared with mothers of VPT infants without fussiness, mothers of VPT infants with fussiness had greater odds of mild depressive symptoms (aOR, 2.32; 95% CI, 1.19–4.53). Similarly, compared with mothers of MLPT and FT infants without fussiness, mothers of fussy MLPT and FT infants had greater odds of moderate-severe symptoms (aOR, 2.30; 95% CI, 1.40–3.80, and aOR, 1.74; 95% CI, 1.40–2.16, respectively). Mothers of MLPT and FT infants with fussiness had increased odds of moderate-severe depressive symptoms, and mothers of VPT infants with fussiness had increased risk of mild symptoms. Early screening for infant fussiness in preterm and FT may help identify mothers with depressive symptoms in need of support.